Understanding financial crises - Allen, Franklin; Gale, Douglas (Oxford : Oxford University Press, 2009)
In this book the authors develop a theoretical approach to analyzing financial crises. Beginning with a review of the history of financial crises and providing readers with the basic economic tools needed to understand the literature, the authors construct a series of increasingly sophisticated models. Throughout, the authors guide the reader through the existing theoretical and empirical literature while also building on their own theoretical approach. The text presents the modern theory of intermediation, introduces asset markets and the causes of asset price volatility, and discusses the interaction of banks and markets. The book also deals with more specialized topics, including optimal financial regulation, bubbles and financial contagion.
Clarendon lectures in finance.
Includes bibliographical references and index.
rpm 09/07/13
Loans
Keywords: Financial crises; Financial contagion; Financial bubbles; Financial regulation